Species composition of the subfamily Stenopodinae (Heterotera: Reduviidae) in Vietnam - Khuong, Dang Duc; Lam, Truong Xuan (Academia Journal of Biology, 2015)
Species composition of the subfamily Stenopodinae (Heterotera: Reduviidae) in Vietnam